HER2 Overexpression and Mismatch Repair Deficiency are Correlated with Malignancy in Colorectal Cancer - Luo, Hai (Cancer Manag Res, 2021)
PURPOSE: This study was designed to investigate the correlation between the expression of human epidermal growth factor receptor 2 (HER2), mismatch repair (MMR), and clinicopathological parameters and serum tumor markers in a total of 522 resection samples materials from colorectal cancer (CRC) patients. These data were also used to determine the links between HER2 and MMR expression and prognosis. METHODS: We conducted a retrospective analysis of the clinical data from 522 CRC patients. Immunohistochemistry (IHC) was used to detect HER2 overexpression and MMR deficiency (dMMR) in tumor specimens which were then correlated with various clinicopathological parameters. Prognostic value for HER2 and MMR expression was then evaluated using the data from 105 CRC patients. RESULTS: HER2 overexpression was identified in 35.63% of the samples evaluated in this study, while the total dMMR rate was 12.64%. Expression of HER2 and several, MMR proteins (MLH1, MSH-2, MSH-6, and PMS-2) were then correlated with tumor location. HER2 overexpression is significantly associated with increased depth of tumor invasion, lymph node metastasis, distant metastases, pTNM staging, vascular invasion, nerve infiltration, and serum carcinoembryonic antigen (CEA) levels. HER2 overexpression and dMMR increased with advancing clinical stage. In addition, deficiencies in MLH1 and PMS2 correlated with HER2 overexpression. Finally, the prognostic evaluations revealed that HER2 overexpression was closely associated with poorer clinical outcomes. CONCLUSION: HER2 overexpression is significantly correlated with multiple clinicopathological parameters resulting in a poorer prognosis. Moreover, the prognosis of patients with HER2 overexpression was worse, confirming its significance during disease assessment. In clinical practice, clinicians should pay close attention to the HER2 profile of patients as they may require more extensive clinical intervention. In addition, deficiencies in MLH1, MSH-2, MSH-6, or PMS-2 correlate with tumor location, and MLH1 and PMS2 expression is associated with lymph node metastasis and pTNM stage, suggesting that these may be additional markers in CRC risk assessments.